In vitro interaction of β-lactams and ciprofloxacin on multiresistant Pseudomonas aeruginosa - Chryssouli, Zoi; Plachouras, Diamantis; Antonopoulou, Anastasia N.; Giamarellou, Helen J.; Giamarellos-Bourboulis, Evangelos J.; Sarafis, Pavlos (My University, 2004)
Increased prevalence of multidrug-resistant (MDR) P. aeruginosa in the nosocomial setting raised the need for the study of any probable susceptibility to the interaction of b-lactams and ciprofloxacin.
Keywords: Resistance; B-lactams; Pseudomonas aeruginosa; Ciprofloxacin